(3TQM eTcd UOhQ ebGdGJ cJGH CbdjOS aj GdGSJbUGJs - (3CMeO Hf YeQ GdcQGHjSis; (3GbdjOSs
(3ChdgG (B:s
(3GdMeO ddg GdPi jMeOg jaJJM GdcdGe , hjPcQ jMdi GdfXGe s
(3BNQgG (B:s
(3bGd CMeO (B: (3GdeYfi ai JKdjK GdfSHI HGdJcQjQ gh NQH GdfSHI ai faSgG aeG MUd ef Pdc agh JKdjK GdfSHI HGdJcQjQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B390 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B58 s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJJg (B(2034) s
Keywords: (3GdQjGVjGJs